Efeito da polinização cruzada no número de sementes dos frutos de tangor Murcott Olé RBC 01 - Campagnollo, Matheus Pozzobom (Universidade Federal de São Carlos, 2021)
The Murcott Olé RBC 01 tangor, resulting from the Murcott Olé RBC irradiation process, shows potential as a table fruit due to its visual aspect, presenting an intense color, small-medium size, and a lower number of seeds per fruit compared to other varieties. . The objective of this work was to study the influence of pollination on the number of seeds in Murcott Olé RBC 01 fruits. The experiment was set up and conducted in the greenhouses of Citrograf Mudas in Ipeúna / SP and the analyzes made in the laboratory of the Centro de Citriculture Sylvio Moreira / SP. Adult Murcott Olé RBC 01 tangor plants were used in pots isolated from other pollinating varieties. The experimental design was randomized blocks, with three replications. Seven treatments were installed where pollens were collected from different varieties: Tangor pollen W Murcott (Verona); pollen of clementine Nules; Valencia orange pollen; tangelo pollen Nova; orange pollen Pear; Murcott Olé RBC 01 tangor pollen and Absence of pollination. A pollen grain viability test was carried out (in vitro pollen germination method). For extraction of pollen grains, large and young closed flower buds were collected, these were kept in Petri dishes with filter paper and kept at 30ºC, for 24 hours, for ripening of the pollen grains. When the Murcott Olé RBC 01 tangor plants were in full bloom, treatments were installed. Evaluations of fruit fixation, number of seeds per fruit and physical-chemical analysis of the fruits were carried out. All treatments proved to be suitable for setting. Fruit fixation was between 19 and 30%, with no statistical difference between treatments. There was no difference in fruit mass and diameter. There was a greater number of seeds in the fruits of the Murcott Olé RBC 01 tangor pollinated with W Murcott tangor pollen. The treatments with the lowest number of seeds were pollination with Murcott Olé RBC 01 tangor, followed by treatment without pollination. There were no significant differences between treatments regarding the analysis of juice yield, acidity, soluble solids and ratio. It is concluded that the fruits of the pollination treatments with Murcott Olé RBC 01 and the absence of pollination presented the lowest number of seeds, showing that the pollen itself and the absence of pollination provide such a characteristic.
Effect of cross-pollination on the number of seeds of Murcott Olé RBC 01 tangor fruits
Keywords: Tangerina; Citros; Melhoramento; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA